PROFILE OF CERVICAL CANCER MORTALITY IN BRAZIL - PERIOD 2010 TO 2015 (CIPEEX, 2022)
INTRODUCTION: CERVICAL CANCER IS CAUSED BY HUMAN PAPILLOMAVIRUS (HPV) INFECTION WITH MOST REPLICATES. THE ONSET OF EARLY SEXUAL LIFE, MULTIPLICITY OF PARTNERS AND MALTREATMENT INCREASES FOR THE DEVELOPMENT OF CERVICAL CANCER. (INCA, 2016). ACCORDING TO THE MORTALITY INFORMATION SYSTEM, IN 2013, THE NUMBER OF DEATHS FROM CERVICAL CANCER WAS 5,430 AND IN 2015, 5725 DEATHS (INCA, 2018). OBJECTIVE: TO TRACE THE MORTALITY PROFILE IN BRAZIL, CENTRAL WEST REGION AND GOIS, FROM 2010 TO 2015. METHODOLOGY: THIS IS A RETROSPECTIVE AND QUANTITATIVE STUDY, USING DATASUS SECONDARY DATA. THE DATA FOR THE STUDY WERE OBTAINED WITH THE HEALTH INFORMATION SYSTEM (DATASUS), SUPPORT ROOM FOR STRATEGIC MANAGEMENT OF THE MINISTRY OF HEALTH (DATASUS). SAGE), AND NATIONAL CANCER INSTITUTE (INCA), SCIENTIFIC AND MANUAL ARTICLES. DATA WERE EXCLUDED FROM ITS CAPACITY AND NO SUBMISSION TO THE RESEARCH ETHICS COMMITTEE WAS REQUIRED. THE STUDY WAS BASED ON DATA FROM WOMEN IN BRAZIL, IN THE CENTER-WEST REGION OF GOIS, OBSERVING AND DESCRIBING THE RELATION OF CERVICAL CANCER IN RELATION TO THE TOTAL NUMBER OF DEATHS USING DETERMINANTS SUCH AS AGE, COLOR, BASIC CAUSE OF DEATH , PLACE OF RESIDENCE AND OCCURRENCES IN THE YEAR 2010 TO 2015. THE ATTACHED DATA WAS INSERTED IN THE MICROSOFT® EXCEL 2010 PROGRAM FOR THE AREA OF €‹€‹GRAPHS AND GRAPHS, WITH THE SAME FREQUENCY AND THE CONSTANTS AND RELATIVE TO THE GRAPH AND GRAPHS. RESULTS: BORN IN THE CENTRAL REGION OF WESTERN BRAZIL, IT IS POSSIBLE TO SHOW THE DEATHS CAUSED BY CERVICAL CANCER ACCORDING TO THE DATES OF 2010-2015, STARTING FROM 15 TO 19 YEARS, WITH 1 DEATH RECORDED IN THIS PERIOD , FROM 20 TO 29 YEARS OLD WITH 65 (0.81%), AGED 30 TO 39 YEARS 338 VICTIMS (4.61%), AGED 40 TO 49 YEARS A TOTAL OF 527 DEATHS (9.05%). , AND HEALTH PROGRESS WAS REPORTED IN 595 (15.09%) WOMEN, AGED 60-69 YEARS, WITH A TOTAL OF 446 WOMEN (19.69%), AGED 70 TO 59 YEARS. 79 YEARS AGO, 335 (28.48%) WOMEN DIED OF CERVICAL CANCER. BETWEEN 2010 AND 2014, IT WAS POSSIBLE TO IDENTIFY ABOUT 730 DEATHS RELATED TO UTERINE CANCER IN THE STATE OF GOIS, AND IN 2013, THE LOWEST NUMBER OF DEATHS OCCURRED IN 2013, AND IN THE YEAR 2014, THE HIGHEST NUMBER WITH 167. CONCLUSION: FINALLY, PREVENTION IS PERFORMED WITH THE AIM OF REDUCING BREAST FLOW. AS A VACCINATION EVEN BEFORE INTERCOURSE.
Keywords: HPV. Cancer of the cervix. Female mortality